Health Education About Intruduction and Prevention of Stunting Using Randai as Local Wisdom Of Minangkabau - Nataria, Desti; Rifni, Indrie Aulia; Wizia, Lady; Salsabila, Adinda Aura (Jurnal Kesehatan - STIKes Prima Nusantara, 2025)
Background: The incidence of stunting in Indonesia in 2022 is 21.6%, while in West Sumatra the incidence of stunting reaches 25.2% of children under five. Adolescent girls are one of the target groups for preventing stunting, through a specific nutrition program, namely providing blood supplement tablets (TTD) for teenagers. 76.2% of adolescent girls get TTD, but 98.6% of teenagers who get TTD do not consume TTD regularly. In Bukittinggi City, the lowest TTD consumption achieved in the Mandiangin Plus Health Center working area was 8.2%, and 42 people out of 367 teenagers experienced anemia. The low consumption of TTD in adolescents is influenced by various factors including knowledge, motivation, self-efficacy, attitudes, parental influence, peer pressure, school policies and commitment.Purpose: to determine the effect of education using the Traditional Minangkabau Art of Randai on teenagers' knowledge and attitudes regarding the recognition and prevention of stuntingMethods: used in this research is quantitative with a pre-experimental design using a pre- and post-test design without control group. The population of this study was 367 young women at SMA 4 and MAN 2 Bukittinggi City in the working area of the Mandiangin Plus Community Health Center, then 79 people were taken as samples taken using simple random sampling. The health education intervention is carried out using traditional randai performance media, then pre- and post-tests will be carried out to measure teenagers' attitudes and knowledge. The analysis used is a paired sample t-test if the data is normally distributed.Results:A total of 397 research articles were screened for eligibility, and 15 articles met the inclusion criteria. Based on the 15reviewed articles, devide into three themes: Nutritional status during preconception, Supplementation during preconception and Lifestyle during preconceptionConclusion: This review found that there are several efforts made in preventing stunting in the preconception period. it is recommended that health workers can optimize the prevention of stunting in the preconception period.